Complexation and transport of alkali, alkaline earth, transition and heavy metal cations by p-tert-butyldihomooxacalix[4]arene tetra(diethyl)amide - Marcos, PM (2015)
The binding properties of the tetra( diethyl) amide ( 2) derived from p-tert-butyldihomooxacalix[4]arene, in the cone conformation, towards alkali, alkaline earth, transition (Mn2+, Fe2+, Co2+, Ni2+, Cu2+ and Zn2+) and heavy (Ag+, Cd2+, Hg2+ and Pb2+) metal cations have been established by extraction studies of metal picrates from an aqueous solution into dichloromethane, transport experiments with the same salts through a dichloromethane membrane and stability constant measurements in methanol. Results concerning the calorimetric study of Na+ and K+ complexes in methanol are presented. The affinity of 2 for some cations (Na+, K+, Ba2+, Ag+ and Zn2+) has been investigated by H-1 NMR spectrometry, as well. The results are compared to those obtained with the analogous calix[4]arene tetraamide derivative 3. Amide 2 displays a preference for the alkali cations (mainly Na+ and K+) in contrast to amide 3 that prefers the alkaline earth cations. Ag+ and Cd2+ soft Lewis acids are also strongly bound by both amides. H-1 NMR titrations confirm the formation of 1: 1 complexes between 2 and all cations studied, also suggesting that they should be located inside the cavity defined by the phenoxy and carbonyl oxygen atoms. 2 shows transport rates that do not follow the same trends as the stability constants or extraction percentages; it can therefore be characterized as a selective receptor.